A Retrospective Study on Outcome of Hemodialysis in Elderly Diabetic Patients - Sana Noor, Hajra Noor, Aishah Ishaque, Shahid Waheed, Syed Imad Hussain, Nadeem Naeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Hemodialysis is a valuable treatment for elderly individuals progressing to chronic kidney disease (CKD). Globally, hemodialysis demand is increasing for elderly individuals as a life-sustaining therapy which might lead to prolonged suffering in geriatric patients. Therefore, the current study aimed to evaluate the outcomes of hemodialysis in elderly diabetic patients. Methodology: This retrospective study was carried out on 64 type 2 diabetic patients admitted to the Dialysis Unit at Social Security Hospital, Multan Road Lahore from January 2021 to April 2022. Ethical approval was taken from the institution research and ethical committee. All the type 2 diabetic patients above 65 years age having CKD on dialysis were included. Patients having disease that require immunosuppressive treatment, history of malignancy, and those who died within three months of initial treatment were excluded. Patient’s survival data and comorbidities such as cognitive, vascular, and autonomy were studied. Other comorbid conditions such as cerebrovascular disease, peripheral vascular disease (PVD), and coronary artery disease (CAD) were reviewed. SPSS version 25 was used for data analysis. Results: Of the total 64 diabetes patients, there were 34 (53.1%) males and 30 (46.9%) females. The overall mean age was 68.9±3.1 years whereas dialysis mean duration was 28±22 months. Cognitive impairment, lost autonomy, and prior cerebrovascular accident had significant association with mortality rate reported as 7.8% per year. The incidence of fistula or graft, depression, dementia, died, and bedridden cases were 39% (n=25), 18.8% (n=12), 15.6% (n=10), 12.5% (n=8), and 14.1% (n=9) respectively. Of the 25 cases of fistula or graft, about 9.5% used catheter. Conclusion: The present study found that mortality rate was 7.8% in elderly (>65 years) diabetes patients. The high mortality risk was substantially related with cognitive disorder, cerebral vascular accident, and lost autonomy. Generally, hemodialysis practice varies with the region’s clinical pattern due to age variation in elderly patients. Keywords: Hemodialysis, Chronic kidney disease, Elderly, Diabetes